Assessing sustainability competencies in contemporary STEM higher education: a data-driven analysis at Tecnologico de Monterrey - Valdes-Ramirez, Danilo; de Armas Jacomino, Laidy; Monroy, Raúl; Zavala, Genaro (Frontiers in Education, 2024)
In contemporary higher education within STEM fields, fostering and assessing sustainability competencies is essential for promoting lifelong learning with a comprehensive understanding of the relationships between innovation and environmental, social, and economic factors. However, training and grading processes for these competencies face significant challenges due to the intricate, adaptable, and multi-modal nature of current academic models. Better understandings and approaches to educating higher education STEM students in sustainability are paramount.Therefore, we have conducted a data-driven analysis on 159, 482 records from 22 STEM programs at Tecnologico de Monterrey between 2019 and 2022, employing data science methodologies.These competencies align with the four dimensions of the UNESCO program "Educating for a Sustainable Future": social, environmental, economic, and political. The study aims to identify the primary challenges faced by students in developing sustainability competencies within this flexible and multi-modal academic environment. Notably, the analysis revealed a widespread distribution of courses with sustainability competencies across all semesters and programs. By the end of the first semester, 93.5% of students had been assessed in at least one sustainability competency, increasing to 96.7% and 97.2% by the end of the second and third semesters, respectively. Furthermore, findings indicate that sustainability competencies are assessed 21 times on average by the end of the sixth semester, with varying levels of development. Interestingly, no significant differences were observed in competency development based on gender, age, or nationality. However, certain competencies such as Commitment to sustainability, Ethical and citizen commitment, and Social Intelligence posed notable challenges across programs and semesters.